2017
DOI: 10.1088/1361-6463/aa9630
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic characteristics of corona discharge generated under rainfall condition on AC charged conductors

Abstract: By synchronous measurement of corona current and the water droplet deformation process on a conductor surface, different types of corona discharge are visualized when AC voltage is applied on a line-ground electrode system. The corona characteristics are closely related to the applied voltage and water supply rate. With the increase of AC voltage, the positive Taylor cone discharge firstly appears and then disappears, replaced by the dripping and crashing discharge. Furthermore, the number of pulses in each pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 19 publications
(25 reference statements)
0
16
0
Order By: Relevance
“…For AC corona, recent studies of the authors have found different possible mechanisms based on a scaled single-drop line to ground setup using high-speed footage. This difference is found to be closely related to the altered response of the water drop under the influence of AC and DC electric field [20], [21]. Under rainfall condition, DC corona discharge is mainly caused by Taylor cone deformation [13].…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…For AC corona, recent studies of the authors have found different possible mechanisms based on a scaled single-drop line to ground setup using high-speed footage. This difference is found to be closely related to the altered response of the water drop under the influence of AC and DC electric field [20], [21]. Under rainfall condition, DC corona discharge is mainly caused by Taylor cone deformation [13].…”
Section: Introductionmentioning
confidence: 94%
“…Thus, a higher rain rate contributes to lower DC audible noise due to an increase in the ionic space charge, shielding the conductor as well as the instability of the Taylor cone [20]. As demonstrated in a recent publication of some of the authors [21], the oscillation of water droplets under AC electric field weakens the stability of Taylor cone formation, and there are two kinds of corona discharge occurring instead. Firstly, for the so-called "dripping" discharge, a gap discharge will occur on the upper side when raindrops dripping on the conductor.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations